The impact of COVID-19 pandemic on dental practice in Iran: a questionnaire-based report - Hanie Ahmadi; Alireza Ebrahimi; Farhad Ghorbani (BMC, 2020)
Abstract Background The highly contagious nature of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV2), besides the fact that dental procedures commonly generate blood and saliva droplets that could lead to the contagion have resulted in the closure of many dental clinics. In the present study, we aimed to evaluate the impact of coronavirus disease 2019 (COVID-19) pandemic on dental practice by conducting an online questionnaire among the Iranian dental practitioners and finding their perspectives on the subject. Methods This report is based on a questionnaire that was conducted among Iranian dentists. The survey included questions that evaluate the dentists' perceptions and attitudes toward the COVID-19 pandemic and its effect on their personal life, financial status, and the quality of dental services for patients. Results Overall, 240 dentists contributed to this study (214 general dentists and 26 specialists). The majority of the participants (n = 170, 70%) did not perform non-emergency procedures during the pandemic. The dental practitioners have suggested several strategies to decrease the risk of contagion, such as reducing treatment sessions (n = 90, 37%), strict triage of patients (n = 156, 64%), and using personal protective equipment (n = 108, 45%). However, most of the dentists (n = 210, 87%) had problems, providing personal protective equipment during the pandemic. Moreover, 97% (n = 234) of the participants reported that they encountered a decrease in their financial income since the eruption of the pandemic. Conclusion Dental health care workers are at the highest risk of contracting COVID-19. Thus, dental practitioners ought to execute the standard protocols more cautiously during the pandemic. They could also lower their work hours and limit dental procedures to emergency treatments to reduce the risk of COVID-19 transmission. Besides, the public organizations should provide proper equipment for the dental practitioners to decrease the risk of contagion.